Preparation, properties and challenges of the microneedles-based insulin delivery system - Chen, Xiang; Wang, Li; Yu, Haojie; Li, Chengjiang; Feng, Jingyi; Haq, Fazal; Khan, Amin; Khan, Rizwan Ullah (Journal of controlled release, 2018)
Microneedle technology relates to pharmacy, polymer chemistry and micromachining. Microneedle can effectively deliver insulin into systemic circulation across the skin. This process does not affect the activity of insulin. Compared to subcutaneous injection, microneedles cause less pain for their special structure. This review thoroughly discusses the preparation technologies of the microneedles-based insulin delivery system including solid, hollow, dissolving, phase transition, glucose-responsive microneedle patches. In the meantime, the properties, challenges and clinical/commercial status of the microneedles-based insulin delivery system are also discussed in this review. [Display omitted]